Prevalencia de Helicobacter pylori y su relación con algunos factores epidemiológicos, en muestras de biopsia gástrica de pacientes que acuden al Hospital Regional de Ayacucho entre mayo a diciembre del 2018 - Cáceres Oré, Gabriela Liseth (2020)
The research was carried out in the Pathology Anatomy Laboratory of the Regional Hospital of Ayacucho. The present work had as a general objective to determine the prevalence of Helicobacter pylori in patients who attended the Regional Hospital of Ayacucho during the months of May to December 2018. The type of research was basic - descriptive with cross-sectional design. 337 gastric biopsy samples were collected and obtained, the samples were processed in the Pathology Anatomy Laboratory of the Regional Hospital of Ayacucho. The prevalence of Helicobacter pylori was determined by the histopathological diagnosis of gastric biopsies (Hematoxylin-Eosin and Giemsa staining), the results were subjected to statistical analysis of Chi square and frequency distribution. It was found that of a total of 337 samples of processed gastric biopsies 208 were positive for histopathological diagnosis, representing a prevalence of 61.7%, being higher in men than in women (65.26% and 57.14%), respectively. The risk factors studied were: type of water consumed: drinking water 60.93%, non-potable water 65.17%, availability of drinking water: at home 61.66%, no water at home 62.50 %, place of disposal of excreta: silo 61.53%, latrine 6.64%, open field 100%, sanitary 59.84%, consumption of alcoholic beverages: if you consume 71.51%, do not consume 68.08%, Tobacco use: if you consume 68.75%, do not consume 75.46%, former smoker 58.33%.